Recent Developments in Instrumentation for Capillary Electrophoresis and Microchip-Capillary Electrophoresis - Felhofer, Jessica L. (2010)
Over the last years there has been an explosion in the number of developments and applications of capillary electrophoresis (CE) and microchip-CE. In part, this growth has been the direct consequence of recent developments in instrumentation associated with CE. This review, which is focused on contributions published in the last five years, is intended to complement the papers presented in this special issue dedicated to Instrumentation and to provide an overview on the general trend and some of the most remarkable developments published in the areas of high voltage power supplies, detectors, auxiliary components, and compact systems. It also includes few examples of alternative uses of and modifications to traditional CE instruments.